Studies of oil product pollution in the aeration zone by mathematical modelling - Ulytsky, Оleg; Dіachenko, Natalia; Sokolov, Armen; Serdіukova, Olga (Visnyk of V. N. Karazin Kharkiv National University. Series Geology. Geography. Ecology, 2023)
Formulation of the problem. The article presents the results of a study to assess the pollution of the aeration zone due to the leakage of oil products as a result of the destruction of the «Amik» oil depot during the military operations in the town of Borodyanka. The destruction of the tanks resulted in an immediate leakage of light oil products onto the soil of the surrounding area. The result was a technogenic environmental situation that required immediate determination of the mechanisms of accidental penetration of pollutants into the soil and groundwater, determination of the area of contamination and scientifically sound methods of soil remediation of oil products. The article highlights the issues of organising mathematical modeling of various data for solving applied problems using Google Earth data.Materials and methods. In order to assess the contamination area and determine the mechanism of accidental penetration of oil products into the soil and groundwater, the existing models of pollutant penetration in case of accidental oil spill were analysed and mathematical spatial models of geomorphological, hydrogeological, engineering-geological and experimental filtration data were created using interpolation, mathematical approximation and gradient analysis. The latter made it possible to identify the directions of surface and groundwater flow both in the local area of the oil depot and in adjacent areas. Using the investigation and filtration parameters obtained during the field work, hydraulic gradients and soil filtration coefficients were calculated, and a spatial mathematical model of the local subterranean gradient of groundwater flow was created.Results. It was shown that the direction of the underground flow is controlled by a zone of local depression, which is expressed by a decrease in the absolute height of the natural lithological layer with a height difference of about 0.4 m or the maximum values of the height of the contamination lens. The direction of extension of this zone has been determined to be from north to south. This zone can be considered the zone of maximum accumulation of liquid with oil products.Based on the survey results, the thickness of the contamination lens was calculated to be 0.3 m on average. Using this indicator, the area of contamination is 4169 m2, the volume of contamination is 1250.7 m3, which corresponds to the claimed damage. However, taking into account the anisotropy of the filtration properties of the lithological types in different directions within the aeration zone, the presence of dissolved water due to dispersion and the presence of local accumulation depressions in the lithological strata, options with other indicators (0.5 m / 0.1 m) are also acceptable. The calculation of the contamination areas was carried out taking into account the power variations. The approximate total areas of oil product distribution in the aeration zone were plotted with reference to Google Earth imagery.Conclusions. The research enabled practical recommendations to be made for cleaning up the area of oil products and preventing the spread of the pollutant by pumping oil products out of the modelled and actually confirmed pollution lens. In accordance with the recommendations, 140 wells were drilled to a depth of 5.2 m, with a diameter of 0.11‑0.168 m and a total length of 710 m, which made it possible to prevent the spread of the contaminant by pumping out the oil products and reusing them after clean-up.